2023
DOI: 10.1186/s13058-023-01624-5
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime changes in body fatness and breast density in postmenopausal women: the FEDRA study

Abstract: Background High mammographic breast density (MBD) is an established risk factor for breast cancer (BC). Body fatness conveys an increased BC risk in postmenopause but is associated with less dense breasts. Here, we studied the relationship between body fatness and breast composition within the FEDRA (Florence-EPIC Digital mammographic density and breast cancer Risk Assessment) longitudinal study. Methods Repeated anthropometric data and MBD paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Thus, the lower likelihood of Asian women experiencing a decrease in mammographic density over time is consistent with the lower extent of weight gain in Asian women and the general inverse relationship between BI-RADS density and BMI. Previous studies showed that gaining weight is indeed associated with longitudinal decreases in percent breast density due to increased amounts of nondense (fatty) breast tissue [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the lower likelihood of Asian women experiencing a decrease in mammographic density over time is consistent with the lower extent of weight gain in Asian women and the general inverse relationship between BI-RADS density and BMI. Previous studies showed that gaining weight is indeed associated with longitudinal decreases in percent breast density due to increased amounts of nondense (fatty) breast tissue [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the available FFDMs, quantitative MBD measures were obtained. The FEDRA study was approved by the Ethics Committee of “Area Vasta Centro” of Tuscany Region and participants signed a specific consent form ( 33 ).…”
Section: Methodsmentioning
confidence: 99%